Cloning and nucleotide sequence of the aroA gene of Bordetella pertussis. - Maskell, D J (1988)
The aroA locus of Bordetella pertussis, encoding 5-enolpyruvylshikimate 3-phosphate synthase, has been cloned into Escherichia coli by using a cosmid vector. The gene is expressed in E. coli and complemented an E. coli aroA mutant. The nucleotide sequence of the B. pertussis aroA gene was determined and contains an open reading frame encoding 442 amino acids, with a calculated molecular weight for 5-enolpyruvylshikimate 3-phosphate synthase of 46,688. The amino acid sequence derived from the nucleotide sequence shows homology with the published amino acid sequences of aroA gene products of other microorganisms.